2020
DOI: 10.1097/cm9.0000000000001208
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-observer variability for the assessment of coronary artery tree description and lesion EvaluaTion (CatLet©) angiographic scoring system in patients with acute myocardial infarction

Abstract: Background: Previously, we developed a novel C oronary A rtery T ree description and L esion E valua T ion (CatLet © ) angiographic scoring system, which was capable of accounting for the variability in the coronary anatomy and assisting in the risk-stratification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Cardiology 2021;146:690-697 DOI: 10.1159/000515759 fuse disease/small vessels are given up to be evaluated [1,2]. Our preliminary study demonstrated that the CatLet score, with a satisfactory reproducibility [3], better predicted clinical outcomes in patients with acute myocardial infarction (AMI) undergoing primary percutaneous coronary intervention (PCI) than the SYNergy between PCI with TAXUS TM and Cardiac Surgery (SYNTAX) score [4]. The clinical variables (CVs), such as age, renal function, and left ventricular ejection fraction (LVEF), also had great impacts on the prognosis of patients with coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 78%
“…Cardiology 2021;146:690-697 DOI: 10.1159/000515759 fuse disease/small vessels are given up to be evaluated [1,2]. Our preliminary study demonstrated that the CatLet score, with a satisfactory reproducibility [3], better predicted clinical outcomes in patients with acute myocardial infarction (AMI) undergoing primary percutaneous coronary intervention (PCI) than the SYNergy between PCI with TAXUS TM and Cardiac Surgery (SYNTAX) score [4]. The clinical variables (CVs), such as age, renal function, and left ventricular ejection fraction (LVEF), also had great impacts on the prognosis of patients with coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 78%
“…At present, there is no unified definition of young AMI. It is generally considered to be a heart disease caused by myocardial ischemia, hypoxia, and necrosis caused by acute occlusion of coronary arteries in adults younger than 45 years old [ 10 ]. According to epidemiological statistics, young AMI patients accounted for 3–10% of the total number of patients with coronary heart disease [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…NRIs for 4.3-year cardiac death and all-cause death were 35.5% (P � 0.0249) and 31.8% (P � 0.0316), respectively [35]. We also reported a satisfactory kappa value greater than 0.8, almost an excellent degree of agreement beyond the level of chance with the CatLet score [36].…”
Section: Remedies For the Syntax Scorementioning
confidence: 54%